Human rights, democracy and Western aid donors’ double standards in Africa: The case of Rwandai - Uwizeyimana, Professor Dominique E. (CENTRAL ASIA AND THE CAUCASUS, 2022)
Dictatorships and pretend democracies characterised by gross human rights violations are not a new phenomenon on the African continent. Literature shows that most African people have never tested the democratic system being enjoyed, and sometimes taken for granted, by most citizens in many western countries. Using examples from some selected African countries, this article argues that some undemocratic regimes which are characterised by human rights violations managed to get and remain in power because of the support they received and continue to get from some major International Finance Institutions (IFIs) and bilateral donors. It also argues that while these institutions claim to use their financial aid to promote democracy and human rights in their rhetoric, they contradict themselves in practice by failing or cutting aid from local institutions that promote democracy or by supporting undemocratic and authoritarian governments despite overwhelming evidence proving that the governments being supported violates human rights of their citizens. While the author recognises that no country should be left to fend for itself in case of emergency or disaster such as a hurricane or earthquake or genocide, one of the main recommendations of this article is that of making human rights and competitive multi- party democracy a cine qua non-prerequisite for any form of aid. The author believes that doing so will create basic conditions for establishing, and possibly upholding, democratic rule in African countries which refuse to willingly establish democratic rule and respect human rights.